-3(2x -2) +5x = -4x + 2(x-1)
-6 + 6 + 5x = -4x - 2x - 2
Your first term on the left side should include x. Your second term on the right side should be positive. This gives you:
$\displaystyle -6x+6+5x=-4x+2x-2$
Grouping like terms, we may write:
$\displaystyle (5x-6x)+6=(2x-4x)-2$
Combining the like terms, we find:
$\displaystyle -x+6=-2x-2$
Can you proceed from here?
No. If you are unsure about your solution, substitute it into the original equation to see if it satisfies the equation. For $\displaystyle x=4$, we get:
$\displaystyle -3(2(4)-2)+5(4)=-4(4)+2(4-1)$
$\displaystyle -3(8-2)+20=-16+2(3)$
$\displaystyle -3(6)+20=-16+6$
$\displaystyle -18+20=-10$
$\displaystyle 2=-10$
This is not true, so the solution is wrong.
We have:
$\displaystyle -x+6=-2x-2$
We may first add $\displaystyle 2x$ to both sides:
$\displaystyle -x+2x+6=-2x+2x-2$
Combining like terms, we find:
$\displaystyle x+6=-2$
Now subtract 6 from both sides, and you get:
$\displaystyle x+6-6=-2-6$
$\displaystyle x=-8$
Now, checking the solution:
$\displaystyle -3(2(-8)-2)+5(-8)=-4(-8)+2(-8-1)$
$\displaystyle -3(-16-2)-40=32+2(-9)$
$\displaystyle -3(-18)-40=32-18$
$\displaystyle 54-40=14$
$\displaystyle 14=14$
This is true so we know the solution is correct.